Analysis of Higher Education Academic Service Satisfaction Levels using the Service Quality and Importance-Performance Analysis methods - Beny Irawan (INFOKUM, 2022)
The academic services of the college today have undergone very significant changes in a very fast time. For these changes, and evaluation of academic services is carried out by measuring the performance of the services provided. To obtain the level of satisfaction, the Service Quality (Servqual) method is used, and to obtain performance from the attributes of the questionnaire to improve its performance, the Importance-Performance Analysis (IPA) method is used. The results of the analysis and data processing using the servqual method at gap 5 showed the gap score gap of each variable so that the Guarantee variable with a score of -0.27, Reliability -0.31, Empathy -0.34, Date Power -0.42 and Tangibles with a score of -0.49. Overall the gap score is -0.37. This shows that any level of service satisfaction expected by students for academic services has not met expectations, as well as the variables of the servqual method. To determine the proposed service improvement based on the attributes of the questionnaire using the Importance-Performance Analysis (IPA) method, 8 attributes are in quadrant I that need to be prioritized for improvement. The attributes are attribute number 4 with a respondent suitability rate of 84.70%, attribute number 5 with a respondent suitability rate of 85.90%, attribute number 10 with a respondent suitability rate of 88.59%, attribute number 15 with a respondent suitability rate of 89.88%, attribute number 16 with a respondent suitability rate of 87.62%, attribute number 17 with a respondent suitability rate of 90.14%, attribute number 18 with a respondent conformity rate of 89.22% and attribute number 27 with a respondent conformity rate of 88.87%.